2019
DOI: 10.3390/catal9010074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Conductivities of Iridium Oxide/Doped SnO2 Oxygen-Evolving Catalysts on the Polarization Properties in Proton Exchange Membrane Water Electrolysis

Abstract: We have developed IrOx/M-SnO2 (M = Nb, Ta, and Sb) anode catalysts, IrOx nanoparticles uniformly dispersed on M-SnO2 supports with fused-aggregate structures, which make it possible to evolve oxygen efficiently, even with a reduced amount of noble metal (Ir) in proton exchange membrane water electrolysis. Polarization properties of IrOx/M-SnO2 catalysts for the oxygen evolution reaction (OER) were examined at 80 °C in both 0.1 M HClO4 solution (half cell) and a single cell with a Nafion® membrane (thickness = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…Yet the differences among supported samples cannot be adequately explained by smaller particle size and thus higher surface area. In addition, several other factors can be responsible for the differences, such as the effect of the support [21][22][23][24]46,56] or difference in Ir-oxide composition (hydrous iridium oxide is more active than the crystalline oxide, which is usually produced thermally). [17,69] Ir/low-TiON x /rGONRs and Ir/rGONRs samples have a very similar structure and composition, as seen from the XRD diffractograms (see the black curves on Figure 1c,d on the graphene-based nanoribbons (2.30 wt% Ti as determined by ICP-OES), a bit smaller average particle size determined with relatively large measurement error (2.3 ± 0.5 nm (Ir/rGONRs) < 3.4 ± 0.5 nm) and the presence of large Ir particles found in Ir/rGONRs (20 nm and more) but not in the Ir/low-TiON x /rGONRs (Figure S6, Supporting Information).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the differences among supported samples cannot be adequately explained by smaller particle size and thus higher surface area. In addition, several other factors can be responsible for the differences, such as the effect of the support [21][22][23][24]46,56] or difference in Ir-oxide composition (hydrous iridium oxide is more active than the crystalline oxide, which is usually produced thermally). [17,69] Ir/low-TiON x /rGONRs and Ir/rGONRs samples have a very similar structure and composition, as seen from the XRD diffractograms (see the black curves on Figure 1c,d on the graphene-based nanoribbons (2.30 wt% Ti as determined by ICP-OES), a bit smaller average particle size determined with relatively large measurement error (2.3 ± 0.5 nm (Ir/rGONRs) < 3.4 ± 0.5 nm) and the presence of large Ir particles found in Ir/rGONRs (20 nm and more) but not in the Ir/low-TiON x /rGONRs (Figure S6, Supporting Information).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…[56] In the case of tin support, doping of the support is also considered a good technique to improve conductivity. [22,55] However, Da Silva et al recently showed that this doping could have a negative impact on the stability of the catalyst. [57] For titanium oxide, exchanging oxide ions for nitride provides sufficient conductivity for electrochemical support, as shown in our previous publications.…”
Section: Introductionmentioning
confidence: 99%
“…IrOx/Nb-SnO 2 synthesized by Ohno et al using the flame pyrolysis method showed a high cell potential of 1.91 V at 1 A cm −2 [15]. Recently, Ramani's group [16] prepared bifunctional Pt-IrO 2 /RuTiO 2 using the co-deposition method; Pt-IrO 2 /RuTiO 2 showed a cell potential of >2 V at 1.5 A cm −2 .…”
Section: Electrocatalytic Performance Analysismentioning
confidence: 99%
“…Thus, water oxidation catalysis of various metal oxides and metal complexes has been investigated in the photocatalytic water oxidation system using a photosensitizer and a sacrificial electron acceptor such as tris(2,2 -bipyridine)ruthenium(II) ion ([Ru II (bpy) 3 ] 2+ ) and persulfate ion (S 2 O 8 2− ), respectively [8][9][10][11][12][13][14][15][16][17][18]. So far, iridium oxide or iridium hydroxide nanoparticles have been reported as the most promising water oxidation catalysts ( Figure 1a) [19][20][21][22][23][24][25][26][27][28]. However, iridium oxide or iridium hydroxide nanoparticles can be deactivated due to agglomeration under harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%